Аналіз систем виявлення та запобігання вторгнень для захисту інформаційних мереж - Михайлова, А. С. (ХНУРЕ, 2024)
This work is devoted to the issues of information security in information networks, namely the analysis of intrusion detection and prevention systems (IDS/IPS). The purpose of the report is a multi-criteria analysis of intrusion detection and prevention systems, taking into account a set of quality indicators. All considered IDS/IPS systems have their own characteristics, so the choice of the optimal system will vary depending on the circumstances, conditions and needs of a particular network
Keywords: запобігання вторгнень; information security